Arctic Environmental Test of Petroleum Handling Equipment (Fuel Purity Monitoring Equipment) - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1970)
The environmental test procedure describes test methods and techniques for evaluating the performance and characteristics of petroleum handling equipment (fuel purity monitoring types) under arctic winter environmental conditions. This evaluation is related to the criteria established by applicable qualitative materiel requirements (QMR), small development requirements (SDR), technical characteristics (TC), or other appropriate design requirements and specifications.